PSYCHOTHERAPY: A COMPARISON OF ABU ZAYD AL-BALKHI AND CBT - Taibah, Scientia Afifah; Hawadi, Lydia Freyani; al-Asyhar, Thobib (Psikis : Jurnal Psikologi Islami, 2023)
Mental health problems are still prominent topics among countries in the last few decades, and Indonesia is no exception. According to the World Health Organization (WHO), a healthy mental state entails individuals realizing and maximizing their potentials, effectively managing life's pressures, excelling in their studies and work, and making meaningful contributions to society. Promotion of the importance of mental health and its treatment has been abundant, but psychotherapy with a religious approach has not received much attention. This study reviews the thoughts of Abu Zayd Al-Balkhi as a pioneer in cognitive therapy, positive psychology, and its relation to the development of Cognitive Behavioral Therapy (CBT) which was first developed by Aaron T. Beck and further developed in the era of modern psychology. There are several similarities in Al-Balkhi's thoughts and the concept of CBT, including views on depression, its symptoms and treatment, as well as the importance of cultivating positive and rational thoughts in treating patients with psychological disorders. The difference between the two lies in the perspective of religiosity instilled by Al-Balkhi, that faith is important in observing worldly problems, and the awareness that true happiness lies in the hereafter. In addition, CBT has undergone significant development both in terms of the disciplinary aspects of psychology and its application in people's lives. The results of this qualitative study are expected to provide an alternative psychotherapy in dealing with mental health problems for Muslim communities.